Penguatan Kesadaran Pekerja Migran Indonesia Terhadap Pentingnya Pendidikan Anak di Hongkong - Wahid Akhsin Budi Nuru Sidiq; Sunyoto; Martanto Setyo Husodo; Latri Setiyaningrum (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Based on official data from Statistics Indonesia's Economic and Financial Statistics for 2024, there are 464,000 Indonesian migrant workers employed overseas, with 3,848,000 of them working in Hong Kong. The high number of migrant workers means that children receive less direct care from their parents. This situation causes children to experience difficulties in their learning and schooling. Based on the problems faced by partners, this community service activity attempts to offer solutions in the form of socialization to raise awareness among migrant workers about children's education and its long-term impact, as well as training and assistance in financial planning for migrant workers in Hong Kong. Community service activities have been carried out in several activities, including coordination with the Special Branch Leader of 'Aisyiyah Hong Kong as a community service partner, and the creation of media in the form of leaflets related to future investment education and access to higher education. Furthermore, community service activities in the form of socialization and training on PMI financial management for children's education were held over two days at the Islamic Centre Hong Kong Mosque, where the Community Service Team also distributed TTG products resulting from faculty community service activities. The community service activities concluded with a visit to the Indonesian Consulate General in Hong Kong to enhance cooperation networks with UNNES.